Tea Chemistry and Pharmacology - Justino, Gonçalo (IntechOpen, 2020)
This book addresses in a succinct way some of the state-of-the-art studies on the chemistry and pharmacology of teas. It starts with some of the reasons why tea is called the elixir of life, and looks at the world consumption of tea and its role in many western and eastern cultures. The book proceeds with a systematic study that establishes the predominant compositions of different types of tea. The effects of tea constituents on health are discussed, and a final chapter discusses some of the potential applications of tea in the food industry.